Early left heart decompression protects the lungs in a canine model of acute left heart failure being treated with venoarterial extracorporeal membrane oxygenation - Chen, Yali; Xu, Tiewei; Zhen, Qin; Gan, Changping; Kang, Yan; Ji, Peng (Frontiers in Cardiovascular Medicine, 2025)
BackgroundNearly 30% of patients who undergo venoarterial extracorporeal membrane oxygenation (VA-ECMO) suffer pulmonary edema, which increases mortality risk. Left heart decompression is widely considered an effective way to counter left ventricular dilatation during VA-ECMO, but whether decompression can protect the lung or improve prognosis is unclear. We investigated this question using a canine model of acute left heart failure being treated through VA-ECMO.MethodsThe left anterior descending artery was ligated in 12 beagles to induce acute heart failure, and starting 1 h later, animals were treated using femoral-femoral VA-ECMO for 3 h. In half the animals, left heart decompression was initiated concurrently with VA-ECMO. In the other half, decompression was initiated 1 h after VA-ECMO began. The “early decompression” and “late decompression” groups were compared in terms of pulmonary function, cardiac function, hemodynamics, histopathology and inflammatory responses.ResultsEarly initiation of decompression led to significantly higher PaO2 (63.27 ± 3.35 vs. 24.70 ± 4.44 mmHg, P = 0.030), lower PaCO2 (31.65 ± 2.87 vs. 41.02 ± 4.88 mmHg, P = 0.014), smaller alveolar-arterial oxygen pressure difference, weaker transpulmonary pressure gradient (3.67 ± 3.14 vs. 13.35 ± 4.26 mmHg, P = 0.017), milder pulmonary edema, lower levels of pro-inflammatory cytokines TNF-α and IL-6 in lungs, lower left atrial pressure, lower left ventricular end diastolic pressure, lower mean pulmonary artery pressure, and higher mean arterial pressure. Earlier decompression also led to milder pulmonary blood congestion and pulmonary histopathology.ConclusionLeft heart decompression, when initiated as soon as possible during VA-ECMO, can protect pulmonary function by alleviating inflammatory responses in the lung, improving hemodynamics and lowering ventricular filling pressure.